2020
DOI: 10.1093/molbev/msaa238
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Diploid Ancestry of the Cultivated Octoploid Strawberry

Abstract: The commercial strawberry, Fragaria × ananassa, is a recent allo-octoploid that is cultivated worldwide. However, other than F. vesca, which is universally accepted one of its diploid ancestors, its other early diploid progenitors remain unclear. Here, we performed comparative analyses of the genomes of five diploid strawberries, F. iinumae, F. vesca, F. nilgerrensis, F. nubicola, and F. viridis, of which the latter three are newly sequenced. We found that the genomes of these species share highly conserved ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 50 publications
4
55
1
Order By: Relevance
“…Edger et al (2019) [13] suggested that the possible progenitors of strawberry were F. vesca, F. iinumae, F. nipponica, and F virdis based on sequence similarity with the wild Fragaria species. However, later reports suggested that F. vesca and F. iinumae were possible progenitors, whereas F. nipponica and F. virdis were not [17,34,35]. The result of our clustering analysis also denied the possibility of F. nipponica and F. virdis as progenitors of the strawberry genome.…”
Section: Assignment Of Chromosome Numbers and Subgenome Names To The Pseudomolecule Sequencescontrasting
confidence: 59%
“…Edger et al (2019) [13] suggested that the possible progenitors of strawberry were F. vesca, F. iinumae, F. nipponica, and F virdis based on sequence similarity with the wild Fragaria species. However, later reports suggested that F. vesca and F. iinumae were possible progenitors, whereas F. nipponica and F. virdis were not [17,34,35]. The result of our clustering analysis also denied the possibility of F. nipponica and F. virdis as progenitors of the strawberry genome.…”
Section: Assignment Of Chromosome Numbers and Subgenome Names To The Pseudomolecule Sequencescontrasting
confidence: 59%
“… Liston et al. (2020) and Feng et al. (2021) challenged the validity of two of the closest available surrogates applied in our study ( F. nipponica and F. viridis ).…”
Section: Resultsmentioning
confidence: 71%
“…iinumae -like, which cast serious doubt on the Liston et al. (2020) or Feng et al. (2021) hypotheses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asterisks indicate significant differences at 0.05 level (*) and 0.01 level (**). Feng et al, 2020). Therefore, BR downstream gene expansion may have resulted from gene duplication and WGD.…”
Section: Genome-wide Identification and Characteristics Analysis Of Bmentioning
confidence: 99%